2021
DOI: 10.3390/ijerph182111177
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Humor-Based Training for Reducing Employees’ Distress

Abstract: An increasing number of studies have demonstrated that humor can impact interpersonal relationships in organizations and employee well-being. However, there is little evidence coming from intervention studies in organizational settings. In response, we developed a training following the principles of positive psychology that aims at improving employees’ adaptive use of humor as a successful mechanism to deal with stress. In this study, we assess the effectiveness of such training and its impact on employee wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Archives of Psychiatry and Psychotherapy, 2023; 4: [30][31][32][33][34][35][36][37][38] Rod Martin [1] defines humour as a fundamentally positive emotion referred to as amusement, triggered by cognitive processes of appreciation of perceived amusing stimuli and non-threatening, funny incongruence, accompanied by specific facial and vocal expressions of laughter.…”
Section: Positive and Negative Aspects Of Employing Humour In Psychot...mentioning
confidence: 99%
“…Archives of Psychiatry and Psychotherapy, 2023; 4: [30][31][32][33][34][35][36][37][38] Rod Martin [1] defines humour as a fundamentally positive emotion referred to as amusement, triggered by cognitive processes of appreciation of perceived amusing stimuli and non-threatening, funny incongruence, accompanied by specific facial and vocal expressions of laughter.…”
Section: Positive and Negative Aspects Of Employing Humour In Psychot...mentioning
confidence: 99%
“…From a physiological perspective, humour elicits laughter, releasing endorphins and relieving stress (Sliter et al 2014). From a communication perspective, humour is considered a pleasant mode of communication that elicits humorous reactions and expressions such as laughter (León-Pérez et al 2021). Laughter and humour often go together, although humour does not necessarily entail laughter (Charaudeau 2006: 20, as cited in Vincent-Durroux 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, among the didactic tools or resources aimed at capturing students' attention to achieve the acquisition of knowledge, humorous resources play an important role, which, due to the emotional effects they generate in students, can facilitate learning [33]. In this sense, the importance of encouraging students through humorous resources has shown that emotions play a fundamental role in education, as well as in stress reduction [34], presenting a pedagogical perspective focused on psychological and neuroscientific aspects, such as learning processes, empathy and social development [35]. In addition, the use of humorous resources in the classroom has proven to be effective in improving classroom dynamics, because it qualitatively increases student participation and fosters their interest, thus developing their critical thinking [36,37].…”
Section: Introductionmentioning
confidence: 99%